Perancangan “Nusa Cita” Aplikasi Permainan Pembelajaran Karakter dan Wawasan Kebangsaan bagi Generasi Z - Dimas Krisna Aditya; Djoko Murdowo; Yanuar Rahman; Andreas Rio Adriyanto; Yoyo Zakaria Ansori (Universitas Hamzanwadi, 2025)
This research is based on lack of understanding of national insight among generation Z, which is caused by conventional learning methods that are less interesting and do not match the habits of generation Z who are accustomed to digital media. Gen Z tends to have difficulty in understanding character and national insight through text-based and lecture-based approaches. The purpose of this study is to develop a prototype of an interactive game-based mobile learning application that presents character and national insight in a more interesting and accessible way. Methode is Research & Development with the Double Diamond model, this study goes through four main stages: Discover (needs analysis), Define (application concept design), Develop (UI/UX design development and interactive features based on gamification), and Deliver (trial and evaluation). The results of the study in the form of the Nusa Cita application, designed by choosing character and Pancasila as a trial, presented through game-based digital media. The use of the Android platform through the gamification approach applied in this application has proven to be able to change the paradigm that games can be an effective tool in the process of transferring knowledge that is more dynamic and not monotonous. However, further research is still needed to perfect the features and optimize the technical and pedagogical aspects so that this application can be widely applied as an innovative learning medium in the digital era.